The management of gallstones in relation to laparoscopic cholecystectomy and gallbladder dyskinesia - Baillie, John (Henry Stewart Talks, 2011)
Gallbladder and biliary disorders, Causes of acute pancreatitis, Cholesterol crystals, Microlithiasis, Problems caused by gallstones, Management of bile duct stones, Endoscopic biliary sphincterotomy, Endoscopic retrograde cholangiopancreatography (ERCP), Gallbladder and biliary dyskinesia, Rome III criteria for diagnosing gallbladder disorders, Algorithm for investigating functional gallbladder disorders